2015
DOI: 10.3354/ame01768
|View full text |Cite
|
Sign up to set email alerts
|

Water column stratification structures viral community composition in the Sargasso Sea

Abstract: Sargasso Sea viral communities at 0 and 100 m are similar in the well-mixed winter, but differ during summer watercolumn stratification.Image: Mya Breitbart and Dawn B. Goldsmith

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 67 publications
(72 reference statements)
3
19
0
Order By: Relevance
“…Evident seasonal succession patterns of microbial communities have been previously described in the Gulf of Aqaba (44,59,60), largely driven by its oligotrophic nature and annual stratification-mixing cycles (59,61,62). Additionally, changes in viral communities have also been observed between different seasons and and between stratified and mixed water column (30,(63)(64)(65)(66).…”
Section: Extended Informationmentioning
confidence: 78%
“…Evident seasonal succession patterns of microbial communities have been previously described in the Gulf of Aqaba (44,59,60), largely driven by its oligotrophic nature and annual stratification-mixing cycles (59,61,62). Additionally, changes in viral communities have also been observed between different seasons and and between stratified and mixed water column (30,(63)(64)(65)(66).…”
Section: Extended Informationmentioning
confidence: 78%
“…Previous studies showed that the composition of viral phoH sequences not only varied throughout the water column but also changed throughout the year in the Sargasso Sea232627. In addition, the composition of viral phoH sequences was also different among six worldwide oceans23.…”
Section: Discussionmentioning
confidence: 99%
“…They found that viral phoH sequences in marine waters were highly diverse, and they identified six novel groups of phoH sequences. Subsequently, they further investigated the viral community composition throughout the water column both in summer and in winter across three years at the Bermuda Atlantic Time-series Study site in the Sargasso Sea, and this study revealed that the distribution patterns of viral communities varied not only with depth but also with time2627. Their findings indicated that phoH is an effective signature gene for examining phage diversity in marine environments.…”
mentioning
confidence: 99%
“…In both cases, after resuspension in ascorbic-EDTA buffer (0.1 M EDTA, 0.2 M Mg, 0.2 M ascorbic acid, pH 6.0), viral particles were concentrated using Amicon Ultra 100 kDa centrifugal devices (Millipore), treated with DNase I (100 U/mL) followed by the addition of 0.1 M EDTA and 0.1 M EGTA to halt enzyme activity, and extracted with the QIAamp DNA Mini Kit (Qiagen 51304). The two remaining water samples were collected from 0 m and 100 m depths at the Bermuda Atlantic Time-series Study site in March 2011, where approximately 180L of seawater were concentrated using a 100kDa tangential flow filter, 0.22 µm-filtered, PEG precipitated, cesium chloride purified, and DNA was extracted using formamide (Goldsmith et al, 2015). All samples were sequenced on an Illumina MiSeq platform at the University of Arizona Genetics Core.…”
Section: Methodsmentioning
confidence: 99%